Understanding the Role of Purinergic P2X7 Receptors in the Gastrointestinal System: A Systematic Review - Cheng, Nathalie; Zhang, Li; Liu, Lu (Frontiers in Pharmacology, 2021)
Background: The role of purinergic P2X7 receptor (P2X7R) is of interest due to its involvement in inflammation and mediating immune cell responses. P2X7R is particularly implicated in the development of inflammatory bowel disease (IBD). However, the extent of the actions of P2X7R in the gastrointestinal (GI) system under physiological and pathophysiological conditions remains to be elucidated. This systematic review aimed to identify, summarize and evaluate the evidence for a critical role of P2X7R in the GI system. Methods: We searched PubMed, Embase and Scopus with search terms pertained to P2X7R in the GI system in disease or physiological state, including “P2X7 or P2X7 receptor or purinergic signaling” in combination with any of the terms “intestine or colon or gut or gastrointestinal”, “pathology or inflammation or disease or disorder”, and “physiology or expression”. Titles and abstracts were screened for potentially eligible full texts, and animal and human studies published in English were included in this study. Data were extracted from papers meeting inclusion criteria. Meta-analysis was not feasible given the study diversity. Results: There were 48 papers included in this review. We identified 14 experimental colitis models, 3 sepsis models and 1 ischemia-reperfusion injury model. Among them, 11 studies examined P2X7R in GI infections, 6 studies on immune cell regulation, 4 studies on GI inflammation, 2 studies on GI malignancies, 3 studies involving intestinal injury due to various causes, 2 studies on ATP-activated P2X7R in the GI system and 2 studies on metabolic regulation. Conclusion: Evidence supports P2X7R mediating inflammation and immune cell responses in GI inflammation, infections and injury due to IBD and other challenges to the intestinal wall. P2X7R inhibition by gene knockout or by application of P2X7R antagonists can reduce tissue damage by suppressing inflammation. P2X7R is also implicated in GI malignancies and glucose and lipid homeostasis. P2X7R blockade, however, did not always lead to beneficial outcomes in the various pathological models of study.